Role of real estate valuation surveyors in the Malaysian National Taxation / Mohd Hasrol Haffiz Aliasak and Mohd Farid Sa’ad - Mohd Hasrol Haffiz, Aliasak; Mohd Farid, Sa’ad (2015)
This paper discussed involvement and role of Valuation Surveyors or Real Estate Valuers in the process of determination of real estate values for national taxation purposes. Valuation Surveyors either in public or private sectors have their own role and functions. Besides that, the position of Valuation Surveyors whether in public or private sectors depends on who instructed them to carry out a valuation exercise. Analysis and evaluation on secondary data were acquired from previous studies, publications, reports and other related journals. The authors also make necessary analysis and evaluation through the provisions as stated in the written laws in Malaysia such as Stamp Act 1949, Real Property Gain Tax Act 1976, Local Government Act 1976, National Land Code 1965 and Income Tax Act 1967. Therefore, the relevant laws and regulation have clearly stated the requirement of valuation surveyors in order to assist the relevant authorities to determine the capital value of chargeable assets (mainly in the form of real estate) before the duties and charges determined by the agencies such as the Inland Revenue Board, Land Offices and local authorities. At the end of this paper, the authors will summarize the types of taxes valuation that require the Valuation Surveyors to determine capital value or rental value.